HUBUNGAN PENGETAHUAN DAN ASUPAN ZAT GIZI DENGAN STATUS GIZI MAHASISWA DIASRAMA UNIVERSITAS ANDALAS - Deni Elnovriza; Hafni Bachtiar; Yenrina Yenrina (Faculty of Public Health, Andalas University, 2009)
Student as human resources is as man who is smart, productive and self-supporting in its duties and to realizing it by fulfilling requirement of nutrient. Living in dormitory they quit of attention of their parents and has independence in determining food which they are consumption as effort to reach nutritional status and optimal health. This research will study the level of student nutrient consumption, to see how far their consumption can fulfill requirement of nutrient suggested and knows factors influencing it. Population in this research is all students living in university dormitory in of Andalas University, school year 2007/2008, with 1 07 samples who consisted of 43 men and 64 women. Analysis descriptively by using technique elementary statistic (based statistic) what depicted in percentage, average and standard deviation and Chi Square test to see relationship between independent and dependent variables. Result of this research shows that 8.4% responder has nutritional status were poor, majority responder (59.8%) has had knowledge about nutrition were good. Average of energy consumption (1706.62 Cal) and carbohydrate (227.56 gram) means less than suggested while intake of protein (56.49 gram) and fat (62.38 gram) have been enough according to sufficiency suggested. There were no relation of nutritional knowledge and average of intake nutrient (energy, protein, fat and carbohydrate) with nutritional status statistically of student living in university dormitory. Management need to facilitate student requirement in dormitory canteen. Next research should be done to know relation between intakes of nutrient with achievement of study, number of illness, and iron deficiency anemic.